Perancangan Aplikasi Media Pembelajaran Bagi Siswa Sekolah Menengah Kejuruan (SMK) Menggunakan Design Thinking - Chan, Eric; Apriyanto (Fakultas Komputer - Universitas Universal, 2023)
Learning media is anything that is used to channel messages or information to the recipient with the aim of stimulating the mind, attention, and interest of learning during the learning process. Therefore, with the development of technology, the world has also developed to follow the changes that occur, especially in the world of education. In the world of education, technology can influence learning media that can support learning activities to be more effective and easier to do. The existence of this learning media application aims to facilitate the learning process and increase efficiency during the learning process, because students only need to access the application to start learning the material that has been provided.